LONGITUDINAL RESEARCH INTO ALZHEIMER'S DISEASE, FRONTO–TEMPORAL DEMENTIA AND OTHER DEMENTIAS. Issue 11 (9th October 2013) - Rossor, Martin; Ahmed, Rebecca; Liang, Yuying; Douglas, Jane; Mahoney, Colin; Warren, Jason; Schott, Jonathan; Fox, Nick
Abstract : Longitudinal studies into Alzheimer's Disease and Fronto–temporal dementia (FTD) is a component of clinical research conducted at the Dementia Research Centre. Methods: Two major longitudinal studies are currently underway 1) Longitudinal research into Alzheimer's disease and other dementias and 2) Familial and sporadic non–Alzheimer's degenerative dementia: longitudinal, clinical, biochemical, and neuroimaging study. Within these studies patients undergo yearly follow–up visits which include clinical assessment, MRI brain imaging, neuropsychological testing and biomarker examination. Patients can be referred directly to the Dementia Research Centre or via the British Neurological Surveillance Unit (BNSU). Participating ordinary and associate members of the Association of British neurology (ABN), who are currently working in the UK, receive a monthly email listing the conditions being surveyed. If the ABN member has seen one of the conditions over the preceding month, they should indicate the number of patients seen via the form on the BNSU section of the ABN website, which will be followed up by the study's investigators. Results: Currently 142 patients are enrolled in the longitudinal research into Alzheimer's disease and other dementias study (15 affected, 72 at risk of familial Alzheimer's disease, and 55 controls), a further 41 patients were previous enrolled, but are now too severely affected to continue. Two hundred and eleven patients are enrolled in the familial and sporadic non– Alzheimer's degenerative dementia study: 125 patients with fronto–temporal degeneration (including cortico–basal degeneration, Pick's disease, Tauopathies, Progranulin and other Ubiquitin associated diseases including motor neuron disease variants and the non–specific frontal degenerations), 20 patients at risk for FTD, 16 patients with Alzheimer's disease (controls), and 50 cognitively normal subjects (controls). Conclusion: The BNSU provides an easy method of referral of patients with dementia for their inclusion in research.